Examining College Student Perceptions of Criminal Justice Outcomes Among Persons With Mental Illness - Dierenfeldt, Rick (International journal of offender therapy and comparative criminology, 2020)
An extensive body of literature has documented punitive responses to mental illness in the United States that have coalesced around arrest and incarceration. Similarly, studies have highlighted the lack of treatment options available to persons with mental illness, as well as the fact the persons with mental illness are particularly susceptible to offering false confessions. Research on perceptions of these realities is, however, comparatively limited. This study contributes to the literature through the use of survey methodology to examine the perceptions of college students at a mid-sized university in the Southeastern United States as they relate to criminal justice outcomes among persons with mental illness. Results of multinomial regression models suggest that these perceptions are shaped by factors such as political orientation, semester standing, and punitiveness.